Meningkatkan Aktivitas dan Hasil Belajar Matematika Menggunakan Model PBL, TGT & MaM - Faizah Helwaniah; Herti Prastitasari (CV. ITTC INDONESIA, 2024)
The research problem is low student activity and learning outcomes in math due to outdated learning models and one-way instruction. The solution is to implement the PBL, TGT, and MAM models. This study aims to assess improvements in teacher and student activities and learning outcomes using classroom action research with quantitative and qualitative methods over 4 meetings. The study involved 18 students from class IVB at SDN Pengambangan 8 Banjarmasin in the 2023/2024 academic year's even semester. Results showed a 100% increase in student activity and learning outcomes by the 4th meeting, demonstrating the effectiveness of the PBL, TGT, and MAM models